The Impact of Corporate Governance on Earnings Quality: Evidence from the UK - WANG, FUWEN (2020)
In recent years, there has been a vast mass of large-scale business failures and scandals in various countries, such as Olympus Corporation, Enron and China Forestry. These high-profile collapses have led stakeholders to question whether the earnings released by the company represent the real picture of the firm’s activities. This study aims to explore the relationship between corporate governance (CG) mechanisms and the quality of earnings in the UK. Seven independent variables are used to represent CG, including board independence, board size, CEO duality, board tenure, audit committee size, audit committee expertise and audit committee meeting. The absolute value of abnormal accruals, a proxy for earnings management (EM), is used to measure earnings quality (EQ). Six control variables, consisting of firm size, leverage, loss, market-to-book ratio, year and industry dummies, are included in the regression model. By using a sample of 68 companies listed on the FTSE 100 from 2015 to 2019, the regression result reveals that board tenure can exert a positive and significant effect on EQ. A negative, while insignificant, result is found between board independence and EQ, which is contrary to previous studies. Besides, all other variables fail to exert a direct influence on EQ. A robustness test is carried out by replacing the original measure of board independence by a dummy variable equals 1 to represent a board with more than half of independent directors and 0 otherwise. Overall, the results are robust.